2008
DOI: 10.1007/s11214-008-9388-2
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric New Particle Formation and the Role of Ions

Abstract: Aerosol particles play an important role in the Earth's troposphere and in the climate system: They scatter and absorb solar radiation, facilitate chemical processes, and serve as condensation nuclei for the formation of clouds. Tropospheric aerosol particles are emitted from surface sources or form in situ from the gas phase. Formation from the gas phase requires concentrations of aerosol precursor molecules aggregating to form molecular clusters able to grow faster than they evaporate. This process is called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 102 publications
0
52
0
Order By: Relevance
“…As a summary, the results indicate that ion-induced nucleation involving ion-ion recombination products have a minor role in boreal forest new particle formation events. Nevertheless, the ion-induced nucleation may have more important role in the particle formation events under substantially different atmospheric conditions or in other locations or altitudes of the atmosphere (Kazil et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a summary, the results indicate that ion-induced nucleation involving ion-ion recombination products have a minor role in boreal forest new particle formation events. Nevertheless, the ion-induced nucleation may have more important role in the particle formation events under substantially different atmospheric conditions or in other locations or altitudes of the atmosphere (Kazil et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (2008) reported that, based on the composition measurements of ambient particles and the independent model calculation, organics can play a dominant role in the growth of particles from a size of 10 to 30 nm as compared to sulfur species. The importance of ion-induced nucleation in the observed new particle formation is under discussion (Kazil et al, 2008). Gagné et al (2008) reported that, on average, the NPF events in Hyytiälä, Finland, were clearly dominated by neutral particle nucleation and ion-induced nucleation had a minor contribution.…”
mentioning
confidence: 99%
“…The aerosol module HAM (Stier et al, 2005) has been extended by a scheme for the treatment of SOA (O'Donnell, 2009). The time integration of the nucleation and condensation schemes has been improved and different nucleation schemes have been implemented and tested (Kazil et al, 2008). HAM2 includes additionally a new impaction and below cloud scavenging scheme.…”
Section: Climate Change Impact On Global Aerosol Cyclingmentioning
confidence: 99%
“…Recently, the relative importance of ion-induced, or ion-mediated, nucleation compared to the atmospheric neutral particle nucleation has been under intensive discussion (Kazil et al, 2008). Thus, we calculated the total 4 nm particle formation rate (J 4 ) from the DMPS data, using measured 4-10 nm particle concentrations, and compared it with the negative 2 nm ion formation rate (J 2NEG ), calculated from the AIS data in a size range of 2-3 nm.…”
Section: Particle Formation and Growthmentioning
confidence: 99%